2020
DOI: 10.1186/s12864-020-06919-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of BeadChip and WGS genotyping outputs using partial validation by sanger sequencing

Abstract: Background Head-to-head comparison of BeadChip and WGS/WES genotyping techniques for their precision is far from straightforward. A tool for validation of high-throughput genotyping calls such as Sanger sequencing is neither scalable nor practical for large-scale DNA processing. Here we report a cross-validation analysis of genotyping calls obtained via Illumina GSA BeadChip and WGS (Illumina HiSeq X Ten) techniques. Results When compared to each other, the average precision and accuracy of BeadChip and WGS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In addition, we prioritized brain eQTLs in regulatory regions unlikely to be covered in array data. Indeed, previous studies have reported that the WGS genotype calling results in higher overall precision for genetic variant analysis [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we prioritized brain eQTLs in regulatory regions unlikely to be covered in array data. Indeed, previous studies have reported that the WGS genotype calling results in higher overall precision for genetic variant analysis [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…The whole protocol was performed in Código 46’s laboratory of human genetics in Mexico. The Infinium HTS protocol has also been used and described in previous works [ 16 ]. All the participants signed an informed consent for the present study and their personal data was anonymized.…”
Section: Methodsmentioning
confidence: 99%
“…Genotypes derived from array and whole genome sequencing data for the same samples should be consistent but are often not. 20,21 To evaluate the consistency of genotyping, we performed a technical comparison of array and WGS data using the same set of samples from COPDGene (n=3,235 with African-American ancestry). The array data were phased independently and integrated with the WGS phased data available in TOPMed, followed by imputation and association testing using genotyping platform as the outcome.…”
Section: Reproducibility Across Genotyping Technologies Copdgene Has Both Array and Wgsmentioning
confidence: 99%